Nano Whiskers ..A “BIG” discussion on “SMALL” things.. - Sharma, Ruchi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Technologyis shrinking fast. Computing technology that would have filled awarehouse 30 years ago can now be squeezed onto a chip a fraction ofthe size of your thumbnail. The very smallest scale of engineering is called nanotechnology. Ananometer is a billionth of a meter, about the width of ten atoms. Nanotechnology may, one day, be capable nanorobotics, nanorobots ornanobots. Working at an almost atomic level, nanobots could buildcomplex items cheaply and repair clothes, equipment and even peoplewithout being noticed. They could also be used to rid the atmosphere ofpollution and to repair holes in the ozone layer.